New Technique of Playing Reong into Musical Composition “Sekunder” | Teknik Baru Memainkan Reong Dalam Komposisi Karawitan “Sekunder” - Gede Prabudinatha Gautama; Ni Wayan Masyuni Sujayanthi (GHURNITA: Jurnal Seni Karawitan, 2022)
Sekunder is a musical composition inspired by the process of cleaning gamelan. The process of cleaning gamelan is not the main activity but an additional activity in gamelan maintenance. Departing from this, the stylist sees a new perspective in composing Karawitan. The use of sandpaper as a means of exploring the sound of the gamelan reong instrument and the role outside of the musician, the soundman, is the object of the creation of the Sekunder composition. The purpose of creating this composition is a new way of playing reong so that later it can become a new technique for playing the reong instrument in the future. The Sekunder work creation method is structured through three stages of creation, namely the assessment, trial, and formation stages. From these three stages, Sekunder is formed into 3 parts where each part describes each of the stages of creation and also the implementation of the process of cleaning the gamelan into a new technique where how to play the reong instrument using sandpaper. The conclusion of this composition is that this composition uses a new technique in playing it, namely using sandpaper where this technique is inspired by the process of cleaning gamelan. In addition, the role of the soundman is very important here as a dynamic regulator. It is hoped that this composition will become the basis for future works and also that new ways of playing reong in this composition can be used continuously.